Radio Frequency Propagation Made Easy - Faruque, Saleh (SpringerBriefs in Electrical and Computer Engineering,, 2015)
This book introduces Radio Frequency Propagation to a broad audience.  The author blends theory and practice to bring readers up-to-date in key concepts, underlying principles and practical applications of wireless communications.  The presentation is designed to be easily accessible, minimizing mathematics and maximizing visuals.